MUSAD-Short – A music-based screening tool to assess autism spectrum disorder in people with intellectual disability. (July 2022) - Tergeist, Marlene; Ziegler, Matthias; Heinrich, Manuel; Sappok, Tanja; Bergmann, Thomas
Abstract: Background: The Music-based Scale for Autism Diagnostics (MUSAD) is an observational instrument for assessing ASD in adults with intellectual disability (ID) and limited verbal abilities. The MUSAD prompts diagnostically relevant behaviors in twelve musical interactional situations. This study explores the psychometric properties of a short version (MUSAD-Short) for ASD screening. Method: Excerpts from 60 videotaped assessments conducted with the original MUSAD were re-coded with a reduced item set. Based on these ratings, items were selected for the MUSAD-Short. Criterion validity of the MUSAD-Short was tested by comparing the MUSAD-Short assignment with the clinical ASD diagnosis. Inter-rater reliability was tested on a subsample of 22 individuals. A dichotomous response format was also examined to investigate whether further simplification is possible. Results: Four situations (congas; ocean drum; symbolic instruments; movement to music) and fourteen items were selected for the MUSAD-Short. The diagnostic accuracy was appropriate, as indicated by sensitivity/specificity values of 73/75% (AUC =0.78). The inter-rater reliability was excellent, measured by the intra-class correlation (ICC) of.77. After item-dichotomization, sensitivity/specificity values were 73/70% (AUC =0.79). Conclusions: The results indicate that the MUSAD-Short provides adequate diagnostic accuracy and sufficient inter-rater reliability. Shortening the original MUSAD is a promising approach to improving the scale's applicability. However, future studies are needed that assess the MUSAD-Short's clinical and psychometric utility in an independent sample. Also, testing its practicability in children and adolescents with ID is indicated. Highlights: A music-based assessment is appropriate for people of all ages and language levels. The original MUSAD is a psychometric sound procedure to support the diagnosis of ASD in adults with ID. The MUSAD-Short has been developed to enhance economy and user-friendliness. First evidence for the MUSAD-Short's psychometric soundness was found. Promising results encourage the adoption of the MUSAD-Short for children and youth.